Centralized approach for multi-node localization and identification - Hasan, Ola A.; Ali, Ramzy S.; Rashid, Abdulmuttalib T. (Iraqi Journal for Electrical and Electronic Engineering, 2017)
A new algorithm for the localization and identification of multi-node systems has been introduced in this paper; this algorithm is based on the idea of using a beacon provided with a distance sensor and IR sensor to calculate the location and to know the identity of each visible node during scanning. Furthermore, the beacon is fixed at middle of the frame bottom edge for a better vision of nodes. Any detected node will start to communicate with the neighboring nodes by using the IR sensors distributed on its perimeter; that information will be used later for the localization of invisible nodes. The performance of this algorithm is shown by the implementation of several simulations .